Eight hands round : a patchwork alphabet - Paul, Ann Whitford; Winter, Jeanette (New York : HarperCollins, 1991)
Introduces the letters of the alphabet with names of early American patchwork quilt patterns and explains the origins of the designs by describing the activity or occupation they derive from.
Keywords: Quilting -- United States -- Patterns -- Juvenile literature; Patchwork -- United States -- Patterns -- Juvenile literature; Quilting; Patchwork; Alphabet